2018
DOI: 10.1051/matecconf/201824403005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the market of electric tractors in agricultural production

Abstract: In Poland, the market of electric field tractors is practically non-existent. There are individual models in offers dedicated to the agriculture made by foreign producers. However, these offers are presented mainly at agricultural fairs. The article presents the research on the needs of farms for electric tractors and presents the possibilities of developing electro mobility in this sector of the economy. Questionnaire was presented, data were collected from those working in the agricultural sector. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…It is their opinion that this, in combination with the unsatisfactory securing of cargo, is endangering the safety of all the road transport participants. Following the adoption of Directive 2014/47 EU, an inspection by the authorities would result in the vehicle being declared roadworthy and the imposition of a fine [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…It is their opinion that this, in combination with the unsatisfactory securing of cargo, is endangering the safety of all the road transport participants. Following the adoption of Directive 2014/47 EU, an inspection by the authorities would result in the vehicle being declared roadworthy and the imposition of a fine [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Within the category of tractors and agricultural machinery, electrification has been pointed out as the next important milestone [70], since the technology has almost reached its optimization limit, but the need for agricultural equipment is increasing due to global population growth. Market research reported in [9] states that the current electric solutions are sufficient only for a small niche of greenhouses and orchards.…”
Section: Tractor and Agricultural Machinerymentioning
confidence: 99%
“…. V" classes [8]; because of these, it is predicted that, sooner or later, ICE-based vehicles could become more expensive than electric and hybrid ones [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the attention focused on an HIL simulation of a hybrid electric orchard tractor to test the proposed load observer energy management strategy. Several studies available in the literature demonstrate the growing interest for tractor electrification [35][36][37][38][39][40] and in general of agriculture machineries. However, low attention is dedicated on the development of software and hardware tools to test specifically designed control strategies which can optimize these new type of powertrains.…”
Section: Introductionmentioning
confidence: 99%